Examining the Factorial Validity of the Entrepreneurial Career Motives Scale: A Five-Nation Comparison - Abdul-Nasiru, I.; Affum-Osei, E.; Goto, S.G.; Yeung, J.C.; Wang, R.; Lam, H.; Chan, D.K.S. (Journal of Career Development, 2020)
This study validates Shane et al.’s Entrepreneurial Career Motives Scale across nations. A total sample of 948 undergraduate and postgraduate students from five nations (China ¼ 229, Hong Kong ¼ 213, Holland ¼ 136, United States ¼ 155, and Ghana ¼ 215) were recruited to complete a survey designed to measure their entrepreneurial motives and other related constructs. Confirmatory factor analysis supported the hypothesized four-factor structure, namely, perceived recognition, sense of independence, pursuit of learning, and perceived roles. Results of the measurement invariance comparisons satisfactorily established measurement equivalence of the scale across nations, language versions, and genders. Both convergent and discriminant validities were established as the motives were associated with different constructs in an expected manner. Interestingly, different patterns in the entrepreneurial career motives emerged across nations. Overall, our findings provide support for the construct validity of the Entrepreneurial Motives Scale. Implications for practice, limitations, and future research directions are discussed.
Research Article
Keywords: entrepreneurship; motives; across nations; entrepreneurial intentions